2006
DOI: 10.1586/14737159.6.6.891
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of biological systems: role of systems biology in medical research

Abstract: Cellular systems are networks of interacting components that change with time in response to external and internal events. Studying the dynamic behavior of these networks is the basis for an understanding of cellular functions and disease mechanisms. Quantitative time-series data leading to meaningful models can improve our knowledge of human physiology in health and disease, and aid the search for earlier diagnoses, better therapies and a healthier life. The advent of systems biology is about to take the leap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 101 publications
0
33
0
Order By: Relevance
“…Kitano suggested that understanding of critical questions in biology required the integration of experimental and computational research [1]. Assmus et al and others maintained that analysis of the dynamics of human relevant networks using predictive computer models and high-throughput data generation would play an increasingly important role in medical research and the elucidation of disease mechanisms [2,3]. However, parametric and structural uncertainty remains an open challenge to mechanistic modeling in medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Kitano suggested that understanding of critical questions in biology required the integration of experimental and computational research [1]. Assmus et al and others maintained that analysis of the dynamics of human relevant networks using predictive computer models and high-throughput data generation would play an increasingly important role in medical research and the elucidation of disease mechanisms [2,3]. However, parametric and structural uncertainty remains an open challenge to mechanistic modeling in medicine.…”
Section: Introductionmentioning
confidence: 99%
“…He suggests that more efforts are needed to promote thorough validation of chemical-specific biomarkers of exposure, the development of reliable and highthroughput phenotypic assays of biomarkers of susceptibility and the formulation of a systems biology approach to the analysis of the modulation of biomarkers by environmental and genetic factors. The latter utilizes mathematical models to describe the structure and behaviour of the biological system (Assmus et al 2006, Hornberg et al 2006. Major systems biology efforts have been applied to cancer in order to understand disease mechanisms and the ability to devise effective therapeutics (Celis et al 2005, Khalil & Hill 2005, Chen et al 2006, Wang et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Despite a surge in the perspectives of using mechanistic mathematical modelling in clinical development [60][61][62][63], parametric uncertainty remains a challenge to mechanistic approaches in medicine [13]. However, contrary to the scarcity of kinetic data, the comprehensive quantification of all concentrations and fluxes within a metabolic system is, at least in principle, experimentally feasible.…”
Section: Discussionmentioning
confidence: 99%